Effect of Heredity and Sparsity on Second‐Order Screening Design Performance. (12th November 2013) - Dougherty, Shane; Simpson, James R.; Hill, Raymond R.; Pignatiello, Joseph J.; White, Edward D.
Abstract : Two recent and powerful screening designs are compared. The comparisons focus on how robust each design is with respect to assumptions of model heredity and sparsity. Four truth models having varied aspects of heredity and sparsity are used; each examined at four levels of random noise. Each screening method is analyzed against the random data using the method's proposed analysis approach and compared in terms of correctly identified model components, incorrectly identified model components (type I error), and missed model components (type II error). Copyright © 2013 John Wiley & Sons, Ltd.